Students’ Perception Towards Teachers Strategies in Teaching Reading Skill - Fatimatuz Zahro; Abdul Aziz Wahab; Fery Ferdiyanto (International Journal of English Education and Linguistics (IJoEEL), 2023)
Students' perceptions towards teachers strategies  in teaching reading skills are also important to know by teachers, so that they can be used as reflections to improving their strategies in teaching reading. This research different between some previous study because the focus in the some previous is more generally because analyze about students’ perception towards teachers attitude, teaching style and attitude in learning English. Meanwhile, in this research is more specifically because analyze about students’ perception towards teachers strategies and only focus in reading skill. In previous study use a quantitative method but in this study use a qualitative method. The aim of this study was to find out how students' perceptions towards teachers strategies in teaching reading skills.The participants in this study were eleventh grade students at SMAI MU Jatiurip. This study used interviews, observation and documentation to obtain data.The result  showed that students’ perception towards teacher’s strategies in teaching reading at SMAI MU  Jatiurip is give had positive percepatan with all of the teaching strategies in teaching reading. They are predicting, question and generating and answering, role plays and think pair share except summarizing strategy because they feel boring about learning reading material when the teacher used summarizing strategy. The most of students prefer to predicting strategy because students understand lessons more quickly when using predicting strategies.